The impact of cartelization on pricing dynamics: Evidence from the German cement industry - Kai Hüschelrath; Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Although the pricing dynamics of hardcore cartels have been studied intensively from a theoretical perspective, empirical evidence is still rare. We combine publicly available data with a unique private data set of about 340,000 market transactions from 36 smaller and larger customers of German cement producers to study the pricing dynamics during and after the breakdown of a German cement cartel. We find that, first, after the breakdown of the cartel, cartel members reduce net prices to a far larger extent than gross prices and that, second, noncartel members slip under the price umbrella of the cartel to increase profits. Our results have important implications for both the design of screening tools to detect cartels as part of public enforcement and the calculation of damages as part of private enforcement of competition law.
Keywords: L41; L61; K21; 330; antitrust policy; cartels; umbrella pricing; net prices; cement; screening; damages; Konzentrationspolitik; Zementindustrie; Kartell; Preis; Beschaffung; Lieferanten-Kunden-Beziehung; Kartellrecht; Rechtsdurchsetzung; Deutschland